2022
DOI: 10.1029/2021gb007278
|View full text |Cite
|
Sign up to set email alerts
|

Global Controls on DOC Reaction Versus Export in Watersheds: A Damköhler Number Analysis

Abstract: The relative capacity for watersheds to eliminate or export reactive constituents has important implications on aquatic ecosystem ecology and biogeochemistry. Removal efficiency depends on factors that affect either the reactivity or advection of a constituent within river networks. Here, we characterized Damköhler number (Da) for dissolved organic carbon (DOC) uptake in global river networks. Da equals the advection to reaction timescale ratio and thus provides a unitless indicator for DOC reaction intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 93 publications
2
12
1
Order By: Relevance
“…We found that in terms of unit area, small catchments (e.g., RB and RT) and especially mountainous catchments (RB) are very efficient DOC exporters (Mattsson et al 2005;Ågren et al 2007;Hilton et al 2011). This is in line with Liu et al (2022), who found that small river networks are DOC export-dominated systems, while very large river networks (stream order 7-9) are DOC reaction-oriented systems.…”
Section: Precipitation Gradient-and Catchment Type-controlled Dischargesupporting
confidence: 86%
See 1 more Smart Citation
“…We found that in terms of unit area, small catchments (e.g., RB and RT) and especially mountainous catchments (RB) are very efficient DOC exporters (Mattsson et al 2005;Ågren et al 2007;Hilton et al 2011). This is in line with Liu et al (2022), who found that small river networks are DOC export-dominated systems, while very large river networks (stream order 7-9) are DOC reaction-oriented systems.…”
Section: Precipitation Gradient-and Catchment Type-controlled Dischargesupporting
confidence: 86%
“…9). The effect of in-stream DOC degradation leading to an increase in the proportion of DIC (or CO 2 ) was suggested to be negligible for catchments in cold (boreal) areas with a low residence time of water in the system (Wallin et al 2010;Liu et al 2022). DOC in our rivers is predominantly coloured and refractory, typical for such boreal landscapes, and thus less prone for rapid photochemical or microbial degradation, so that within river losses of DOC had no major influence here.…”
Section: Precipitation Gradient-and Catchment Type-controlled Dischargementioning
confidence: 81%
“…was not found to be as important in regulating the trend in C DOC (see Figure S14). This finding contradicts with what was previously hypothesized (Liu, Maavara, et al, 2022;Xu & Xu, 2022) but is in agreement with results by Gommet et al (2022) for the European river network. The regional analysis of the relationship between temperature and C DOC also indicates that temperature is only weakly and positively related to C DOC for most basins (Figure S23).…”
Section: Decadal Trendscontrasting
confidence: 82%
“…Nutrient removal rate is depending on both nutrient uptake velocity and hydrological parameters, such as stream depth and retention time. Values of italicvf$$ vf $$ for nutrients are often considered constant in small headwater streams (Liu et al, 2022) and we assumed that the errors in stream nutrient removal caused by varied nutrient italicvf$$ vf $$ were ignorable in the YRC (Table 3) (Ensign & Doyle, 2006; Mulholland et al, 2008; Wollheim et al, 2006).…”
Section: Discussionmentioning
confidence: 99%